1997
DOI: 10.1007/bf02439718
|View full text |Cite
|
Sign up to set email alerts
|

The cochlear aqueduct in pediatric temporal bones

Abstract: The cochlear aqueduct is a bony channel which contains the fibrous periotic duct and connects the perilymphatic space of the basal turn of the cochlea with the subarachnoid space of the posterior cranial cavity. Previous histological studies suggested that patency depended on age, whereas a more recent study showed no statistical correlation between age and patency. To clarify patency in pediatric cochlear aqueducts, we selected 21 temporal bones from 12 infants and children, varying in age from birth to 9 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
9
1
1
Order By: Relevance
“…no age related changes. Bacher et al made histologic sections of the CA in paediatric temporal bones, they found a short and patent CA in newborns and a significant increasing length with growth [13]. In the same year, Gopen et al [3] stated that there was no correlation between age and narrowest diameter or between age and category and of patency, also using histologic sections.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…no age related changes. Bacher et al made histologic sections of the CA in paediatric temporal bones, they found a short and patent CA in newborns and a significant increasing length with growth [13]. In the same year, Gopen et al [3] stated that there was no correlation between age and narrowest diameter or between age and category and of patency, also using histologic sections.…”
Section: Methodsmentioning
confidence: 96%
“…Even in newborns, the CA is continuously detectable and increases in length during the growth period [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the sample studied, there was no evidence of pathology, since all CA were pervious. In spite of the description of variability [2,12] the measurements depend on the technique. The infundibular form of the CA opening and its anatomical variations may give rise to problems in the determination of the depth of reference points [2,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Measures of width of adult dissected bone were obtained within the opening of the funnel with values from 0.5 to 3.0 mm [1,4]. Using histological techniques the diameter in adults varied from 0.7 to 2.1 mm [10,11] with similar values from newborns and infants from 0.7 to 2.3 mm [12,13]. Image studies showed values from 2.0 to 6.7 mm in infants [2,7,9,14] and from 0 to 11 mm in adults [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation